A multifunctional targeted nanoprobe with high NIR-II PAI/MRI performance for precise theranostics of orthotopic early-stage hepatocellular carcinoma. Issue 42 (12th October 2021) - He, Linyun; Zhang, Yachao; Chen, Jiangbo; Liu, Gongyuan; Zhu, Jingyi; Li, Xiaozhen; Li, Dengfeng; Yang, Yuqi; Lee, Chun-Sing; Shi, Jiahai; Yin, Chao; Lai, Puxiang; et al.
Abstract : A novel GPC-3-targeted multifunctional nanoprobe for precise theranostics of orthotopic early-stage hepatocellular carcinoma was developed via dual-modal photoacoustic/magnetic resonance imaging and imaging guided non-invasive photothermal therapy. Abstract : Early diagnosis and effective treatment of hepatocellular carcinoma (HCC) is quite critical for improving patients' prognosis. The combination of second near-infrared window photoacoustic imaging (NIR-II PAI) and T 2 -magnetic resonance imaging ( T 2 -MRI) is promising for achieving omnibearing information on HCC diagnosis due to the complementary advantages of outstanding optical contrast, high temporospatial resolution and soft-tissue resolution. Thus, the rational design of a multifunctional targeted nanoplatform with outstanding performance in dual-modal NIR-II PAI/ T 2 -MRI is particularly valuable for precise diagnosis and imaging-guided non-invasive photothermal therapy (PTT) of early-stage HCC. Herein, a versatile targeted organic–inorganic hybrid nanoprobe was synthesized as a HCC-specific contrast agent for sensitive and efficient theranostics. The developed multifunctional targeted nanoprobe yielded superior HCC specificity, reliable stability and biocompatibility, high imaging contrast in both NIR-II PAI and T 2 -MRI, and an excellent photothermal conversion efficiency (74.6%). Furthermore, the theranostic efficiency of the targeted nanoprobe was systematically investigated using the orthotopic early HCC-bearing mice model. The NIR-II PAI exhibited sensitive detection of ultra-small HCCs (diameter less than 1.8 mm) and long-term real-time monitoring of the tumor and nanoprobe targeting process in deep tissues. The T 2 -MRI demonstrated clear imaging contrast and a spatial relationship between micro-HCC and adjacent structures for a comprehensive description of the tumor. Moreover, when using the targeted nanoprobe, the non-invasively targeted PTT of orthotopic early HCC was carried out under reliable dual-modal imaging guidance with remarkable anti-tumor efficiency and biosafety. This study provides an insight for constructing a multifunctional targeted nanoplatform for precise and comprehensive theranostics of early-stage HCC, which would greatly benefit the patients in the era of precision medicine.